2011
DOI: 10.1161/strokeaha.111.621581
|View full text |Cite
|
Sign up to set email alerts
|

Chronically Epileptic Human and Rat Neocortex Display a Similar Resistance Against Spreading Depolarization In Vitro

Abstract: Background and Purpose-Experimental and clinical evidence suggests that prolonged spreading depolarizations (SDs) are a promising target for therapeutic intervention in stroke because they recruit tissue at risk into necrosis by protracted intracellular calcium surge and massive glutamate release. Unfortunately, unlike SDs in healthy tissue, they are resistant to drugs such as N-methyl-D-aspartate-receptor antagonists. This drug resistance of SD in low perfusion areas may be due to the gradual rise of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 35 publications
5
42
3
Order By: Relevance
“…By contrast, both repeated IEEs and SDs seem to have inhibiting or ''anti-kindling'' effects on SD; supporting evidence includes the following: (1) in various models, the susceptibility to SD decreased during epileptogenesis (Kö hling et al, 2003;Maslarova et al, 2011;Tomkins et al, 2007), (2) SDs do not invade penicillin-induced epileptic foci but typically circulate around them (Koroleva and Bures, 1979), (3) single daily SDs induced for 1 or 2 weeks in mice decreased the susceptibility to SD (Sukhotinsky et al, 2011), and (4) even within the same cluster of SDs, subsequent SDs typically propagate through a smaller region than the first SD (James et al, 1999). In the light of these observations, it appears that there are strikingly different types of pathologic hyperexcitability states in the brain which can be associated with either increased or decreased susceptibility to SD.…”
Section: The Known Experimental Triggers Of Sd Are Either Potentiallymentioning
confidence: 89%
See 1 more Smart Citation
“…By contrast, both repeated IEEs and SDs seem to have inhibiting or ''anti-kindling'' effects on SD; supporting evidence includes the following: (1) in various models, the susceptibility to SD decreased during epileptogenesis (Kö hling et al, 2003;Maslarova et al, 2011;Tomkins et al, 2007), (2) SDs do not invade penicillin-induced epileptic foci but typically circulate around them (Koroleva and Bures, 1979), (3) single daily SDs induced for 1 or 2 weeks in mice decreased the susceptibility to SD (Sukhotinsky et al, 2011), and (4) even within the same cluster of SDs, subsequent SDs typically propagate through a smaller region than the first SD (James et al, 1999). In the light of these observations, it appears that there are strikingly different types of pathologic hyperexcitability states in the brain which can be associated with either increased or decreased susceptibility to SD.…”
Section: The Known Experimental Triggers Of Sd Are Either Potentiallymentioning
confidence: 89%
“…The potassium threshold for SD in neocortical slices is between $12 mM in young and $16 mM in older animals (Maslarova et al, 2011). The threshold seems to be in a similar range in neocortex in vivo (Petzold et al, 2005b), but due to glial buffering, the potassium gradient between artificial cerebrospinal fluid (ACSF) and cortex is steep when potassium is applied topically to the brain.…”
Section: The Known Experimental Triggers Of Sd Are Either Potentiallymentioning
confidence: 99%
“…Among the differences is an anti-thetic susceptibility to spreading depolarization. It was thus demonstrated recently that the potassium threshold for spreading depolarization was not lowered but markedly elevated in neocortex slices from chronically epileptic rats compared with agematched controls, and this threshold of chronically epileptic rodent tissue was in fact similarly high as that of neocortex slices from patients with intractable epilepsy [103]. In a similar fashion, Köhling and colleagues reported that the GABA A receptor antagonist bicuculline readily induced spreading depolarizations in neocortex slices from healthy rats whereas, in chronically epileptic neocortex slices from rats or patients, bicuculline failed [102].…”
Section: A Brief History Of Spreading Depolarizationmentioning
confidence: 98%
“…13 On the other hand, the aging nervous tissue proves to be increasingly resistant to experimental SD elicitation, requiring rising concentration of K þ to trigger SD. 14,15 Similarly, the likelihood of spontaneous SD occurrence in the ischemic rat cortex decreases with age. 16 It is, however, uncertain at what age the threshold of SD elicitation starts to rise, especially in ischemic tissue.…”
Section: Introductionmentioning
confidence: 95%